Pemberdayaan dan Pengembangan UKM sebagai Pendorong Ekonomi Desa (Studi Kasus pada Desa Kramat Gajah, Kecamatan Galang, Sumatera Utara) - Ayu Permata Sar Sari; Mardina Ratna Sari Ritonga; Rahmah Aulia; Wahyuni Syahfitri; Heri Firmansyah (Dinamisia : Jurnal Pengabdian Kepada Masyarakat, 2022)
SMEs or Small and Medium Enterprises in national economic development because small companies are in economic growth, in term of the economic crisis that occurred in the country caused by the Covid-19 pandemic, which collapsed many on a large scale, Small and Medium Enterprises (SMEs) proved to be more resilient in the face of a crisis. Small and Medium Enterprises (SMEs) Mawar Indah is located in Kramat Gajah Village, Galang, North Sumatra, Has problems and obstacles in terms of selling products widely due to limited skills and product socialization. Thus, the UINSU Group 28 Community Service Program conducted a program to improve product quality, product packaging, product quality, socialize the importance of halal certification and labeling, as well as Digital Marketing training through E-commerce and social media as well as collaboration. The method carried out is based on service and empowerment with Participatory Action Research with three main steps, namely reflection and socialization, Planning and evalution. This program can improve the quality and productivity of Small and Medium Enterprises (SMEs) so as to encourage the rural economy.